Identification documents and their significance for controlling a person released from punishment under probation - Чабаненко, Т. В. (Problems of legality, 2014)
This article deals with issues such as what documents should be considered as identification documents and what significance they have for controlling a person released from punishment under probation by criminal and penal inspection and proposes an option of how to decide this problem in case a convict does not have them through corresponding amendments to the applicable legislation.